Understanding Reading Themes and Question Types in JLPT N5: Insight from Practice Books - OPI SUKARDI PUTRI; Hayati, Novia; Juangsih, Juju (Universitas Negeri Semarang, 2025)
This qualitative study reports on the investigation of theme or topics and types of questions in the reading section of the JLPT N5. Drawing on 37 texts and 46 questions from three different book sources of JLPT N5 practices, this research reveals three main findings. First, apart from informational texts, which are realized in the forms of short notices such as announcements, timetables, food labels, and memos, most topics in the short and longer texts tend to be personal and descriptive. Second, all topics in the reading section are related to everyday life, involving 11 topics related to personal life and to the surroundings. Personal-related topics include activities (past, present, and future), family, future dreams, houses, friends, pets, and simple experiences, whereas surroundings-related topics are composed of announcements, timetables, instructions, and food labels. The most dominant topic is descriptions of activities (past, present, and future), while the second highest topic is related to the announcement content (including the name of the place, operational hours, contact numbers, lists of products, prices, discount information, and warnings about something). Third, the types of questions in the reading section of JLPT N5 involve three categories: easy, moderate, and difficult. Easy types of questions include locating certain information, such as names, objects, activities, and basic facts within a text and/or simple matching visuals with texts. Moderate questions cover matching texts and visuals, reasoning, and finding details. The difficult types of questions involve conclusion, prediction, and inference, in which the examinees are required to understand what is not explicitly stated to answer.